Effect of Ash from Forest Fires on Leaching in Volcanic Soils - Escudey-Castro, A; Escudey-Castro, A; Pizarro-Arriagada, C; Pizarro-Arriagada, C; Arancibia-Miranda, N; Arancibia-Miranda, N (Elsevier B.V., 2015)
In Chile, significant amounts of native forests as well as pine and eucalyptus plantations are lost yearly as a result of forest fires. Besides the effect of high temperatures on the soil and destruction of the plant cover, the ashes originating from these fires end up spread out over the soil. The effects associated with the distribution of ash produced by burning of native forests, pine plantations, or eucalyptus plantations were studied over five different types of soil of volcanic origin by means of leaching columns. Testing columns 25-cm deep were prepared at each soil bulk density; 30 g of ash was added to the top of the column and irrigated by adding one pore volume of water every week for 12 weeks. Control soil and ash columns were prepared and treated similarly. Leachates were collected weekly and the pH, organic carbon (OC) content, and concentration of various cations and anions were analyzed (via ICP and HPLC); at the end of the experiments all columns were cut into 5 cm sections and the residual soil was analyzed. In general, Na+, Ca2+, K+, and Mg2+, and Cl-, NO3-, and SO42- were the most significant cations and anions in the leachates respectively, with concentrations on the order of mmol. Most of the PO43- (99%) was retained in the column. Trace elements (Cu2+, Zn2+, Pb2+, and others) were absent in the leachates in concentrations on the order of μmol; Fe3+ and Al3+ were the most significant metals in the leachates, and their presence was most relevant in Andisols. Dissolved OC in the soil, due to the alkaline nature of the ash, was mostly retained at soil depths of 25cm. Because of the ashes, an increase in the leachate pH was observed, with the most significant increase occurring in Andisols during the first 1-6 pore volumes of irrigation. At the end of the experiment, soil pH was higher in the ash-treated columns at depths of 0 to 15cm but similar to the pH of control columns at depths of 20-25cm, confirming the high buffer capacity of the soils. © 2014 Elsevier B.V.